TROOPS MANAGEMENT BASED ON FEEDBACK - Victor E. Bobylov (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The article describes and analyzes the concept of feedback and its influence on the troops management during warfare. Positive and negative sides were identified. Based on the analysis the approaches to the using feedback in the course of command and control are offered. The proposed approaches will enable the officers of the military management to reconsider their views on the decision-making process during command and control in the course of conducting operations.